Analysis of crack propagation in onshore wind turbine foundations using the double-K fracture model. (July 2022) - Amponsah, Evans; Wu, Zhiquan; Feng, Qiang; Wang, Zhenyu; Kwame Mantey, Selase
Highlights: Pullout tests on sub-part models are used to study the uplift resistance of the tower-foundation connection of onshore wind turbine. The double-K fracture propagation criterion is applied to study the fracture behaviour of onshore wind turbine foundations. The fracture behaviour of onshore wind turbine foundation is sensitive to the embedment depth of the steel ring and shear reinforcement ratio. A method to predict the stage of crack propagation and safety of onshore wind turbine foundation is proposed. Abstract: The load-bearing mechanism of the embedded steel ring to foundation connection used for onshore wind turbines causes high stress concentrations in the concrete around the base flange. Cracks initiate and propagate through the foundation from the base flange. The crack growth under normal operating and extreme loading conditions reduces the stiffness and load-bearing capacity of the tower to foundation connection. This in turn affects power production and could lead to economic losses if failure of the foundation occurs. This paper investigated the stability of a horizontal crack propagation in a typical onshore wind turbine foundation using the double-K fracture propagation criterion. The study involved experiments on two sub-part models and numerical simulation of a large-diameter onshore wind turbine foundation. Using the numerical results, the stress intensity factors at the tip of a horizontal crack emanating from the outer edge of the base flange were calculated at different stages of loading. The stress intensity factors were compared with the initial and unstable fracture toughness of concrete to assess the stability of the crack propagation. It was found that for vertical displacements of the embedded steel ring exceeding 9 mm, the crack propagation became unstable. Based on the crack propagation behaviour, a method was proposed to assess the safety of onshore wind turbine foundations using the vertical displacements of the embedded steel ring.